Hypopharyngeal carcinoma with skeletal muscle metastases: a rare clinical entity - Sharudin, Nurafiqah; Jeet Kaur, Malinda; Sai Guan, Lum; Hitam, Shahrul; Anuar, Khairullah; Hassan, Eyzawiah; Yusuf, Rosna (International Surgery Journal, 2022)
The common sites of distant metastatic spread of head and neck malignant tumor are lungs, liver, and bones. Skeletal muscles metastases are extremely rare. We present a case of 61-year-old man who was previously treated with radical chemo radiotherapy for hypopharyngeal squamous cell carcinoma, stage T4bN2cM0. During surveillance follow up 21 months post treatment, he developed a right proximal arm mass. There were no neurological or vascular deficit. MRI revealed an irregular enhancing intramuscular soft tissue mass within the right triceps muscle, with widespread nodal and skeletal muscle metastases. Tissue biopsy revealed a metastatic carcinoma favoring poorly differentiated squamous cell carcinoma. He received palliative chemotherapy but died 4 months later. Skeletal muscle metastases must be high in the list of differential diagnosis in a head and neck cancer patient presented with a muscle mass, even though it is rather rare. Radiological imaging and tissue biopsy helped in the diagnosis and prompt management.